Pengaruh Budaya Organisasi Dan Disiplin KerjaTerhadap Kinerja Pegawai Pada Inspektorat Daerah Provinsi Kalimantan Timur - mahdaniah mahdaniah; Achmad Efendi; Damingun . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study explores how organizational culture and work discipline influence employee performance at the Regional Inspectorate of East Kalimantan Province. The research is driven by problems such as low employee initiative, poor internal communication, and delays in e-performance input. A quantitative approach with multiple linear regression analysis was applied. Data were collected through questionnaires from 86 respondents and analyzed using SPSS version 29. The findings show that both organizational culture and work discipline have a significant and positive effect on employee performance. Internal communication is the dominant aspect of culture, promoting coordination and a supportive work atmosphere. Discipline affects task completion quality and punctuality. The regression model indicates that 67.1% of performance variation is explained by these two variables. These results emphasize the importance of building strong cultural values and enforcing discipline to improve performance and accountability in public institutions.